Features of Ukraine’s Trade Cooperation in the Current Conditions of Globalization - Ptashchenko Olena V.; Vovk Volodymyr A. (Bìznes Inform, 2021)
The article considers the main features of the high-tech sphere and the possibility of trade cooperation therein. Technological progress has completely changed the structure of the modern world economy. Thanks to the technologies, novel activities have been developed, many of which are efficient and highly profitable. A classic example of the impact of the introduction of high technologies in everyday life is the emergence and use of new information technology. Due to the widespread use of new communication technology, the transmission cost of voice, data, text, images, as well as international fees for the transmission of information have sharply decreased. Fast data transfer (e.g. e-mail, via the Internet) and teleconferences have provided economy with modern communication and the ability to do business around the world, allowing to significantly increase the speed of operations and thus receive increased profits. According to the Ministry of Economic Development, Trade and Agriculture of Ukraine, trade cooperation in the high-tech sphere can be divided into several directions: IT industry, defense industry, energy complex, aerospace industry. Thus, about 85% of energy and oil and gas equipment is exported during a year. The main export destinations are Russia, Kazakhstan, Turkmenistan, Uzbekistan, Azerbaijan and the UAE. Therefore, energy, oil and gas companies are less susceptible to the crisis in the economy over the past few years. This is due to the fact that the work of enterprises in these sectors is mainly based on long-term contracts, most of which serve projects for the construction of gas pipelines, oil pipelines and the reconstruction of power plants. Such projects continue to be financed by Central Asian countries. Despite some significant successes in such industries as aerospace, energy equipment production, heavy and transport engineering, and some others, the state of the industry in general does not meet the modern requirements of both the domestic and the world economy. First of all, Ukraine lacks a number of high-tech industries that determine export positions. The quality and technological solutions of electronic products, household appliances, agricultural and road-building machines, as well as a number of other goods are significantly inferior to foreign counter-parts. Technological exchange or trade cooperation in the high-tech sphere in a broad sense can be understood almost the entire range of international economic relations, including the purchase and sale of patents and licenses, trade in goods and services.